2013
DOI: 10.1097/olq.0000000000000002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing HIV/AIDS, Viral Hepatitis, Sexually Transmitted Disease, and Tuberculosis Prevention in the United States Through Program Collaboration and Service Integration

Abstract: HIV infection, viral hepatitis, sexually transmitted diseases, and tuberculosis in the United States remain major public health concerns. The current disease-specific prevention approach oftentimes has led to narrow success and missed opportunities for increasing program capacity, leveraging resources, addressing social and structural determinants, and accelerating health impact-suggesting a need for greater innovation to prevent related diseases. The National Center for HIV/AIDS, Viral Hepatitis, STD, and TB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Moreover, STIs, perhaps with the exception of HSV-2, tend to be less stigmatizing than HIV, which may encourage HHR to seek out STI testing in these types of circumstances ( 65 ), highlighting the important role of STI testing in achieving the goal of HIV elimination ( 66 ). Yet at present, the STI and HIV prevention systems in the US are considered “siloed” or largely separate, which may lead to missed opportunities for comprehensive sexual health services ( 67 ). In fact, public health system leaders in the US have called for better integration of STI and HIV services to improve the early diagnosis of a range of sexually transmitted health problems ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, STIs, perhaps with the exception of HSV-2, tend to be less stigmatizing than HIV, which may encourage HHR to seek out STI testing in these types of circumstances ( 65 ), highlighting the important role of STI testing in achieving the goal of HIV elimination ( 66 ). Yet at present, the STI and HIV prevention systems in the US are considered “siloed” or largely separate, which may lead to missed opportunities for comprehensive sexual health services ( 67 ). In fact, public health system leaders in the US have called for better integration of STI and HIV services to improve the early diagnosis of a range of sexually transmitted health problems ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus concerns about STIs and STI testing can play important roles in achieving the goal of HIV elimination. Yet the STI and HIV prevention systems are largely “siloed,” which may lead to missed opportunities for comprehensive sexual health services that consider both STIs and HIV infection [ 60 , 61 ]. The CDC has called for better integration of STI and HIV services to improve the early diagnosis of a range of sexually transmitted health problems [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…At risk individuals are recommended to get tested at least once a year [11]. Routine HIV testing can be used to identify persons infected with HIV who have yet to receive the diagnosis and to link them with primary and secondary prevention services [15]. Previous studies have shown the persistent and unequal distribution of HIV across the US population by age, race, sex, and Socioeconomic Status (SES) [1618].…”
Section: Introductionmentioning
confidence: 99%